Home Environment, Socio-cultural Characteristics, and Nutrition Knowledge of Users of a Soup Kitchen and Food Pantry - Mousa, Tamara; Freeland-Graves, Jean H. (Jordan Journal of Agricultural Sciences, 2022)
The present cross-sectional study examined the home environment, socio-cultural characteristics, and nutrition knowledge of 222 clients of a soup kitchen and food pantry. Participants completed a demographic questionnaire, Multidimensional Home Environment Scale, and Nutrition Knowledge Scale. The food pantry population consisted of more women, Blacks, Hispanics, and older clients than did those from the soup kitchen. Soup kitchen clients also exhibited lower socioeconomic status, and were mostly homeless, as compared to those of the food pantry. Both groups had a low level of nutrition knowledge (55%). Furthermore, most of the food pantry recipients were non-smokers and non-alcohol-drinkers, as compared to about half of the soup kitchen participants, who had lower availability of healthy foods at home and 50.9% of them consumed American foods. Thus, future research is essential to assess the impact of the home environment, socio-cultural influences, and nutrition knowledge on diet quality and food security of food recipients in the U.S.